Streptobacillus moniliformis and IgM and IgG Immune Response in Patient with Endocarditis - Philipp Mathé; Katja Schmidt; Viktoria Schindler; Ahmad Fawzy; Tilman Schultze; Reinhard E. Voll; David Pauli; Milena Popova; Franziska Schauer; Tobias Eisenberg (Emerging Infectious Diseases, 2024)
We describe a case of endocarditis caused by Streptobacillus moniliformis bacteria, a known cause of rat-bite fever, in a 32-year-old woman with pet rats in Germany. The patient had a strong serologic response, with high IgM and IgG titers. Serologic analysis is a promising tool to identify S. moniliformis bacterial infection.